2011
DOI: 10.1100/2011/794801
|View full text |Cite
|
Sign up to set email alerts
|

Nanoexposure, Unusual Diseases, and New Health and Safety Concerns

Abstract: Accumulating studies in animals have shown that nanoparticles could cause unusual rapid lung injury and extrapulmonary toxicity. Whether exposure of workers to nanoparticles may result in some unexpected damage as seen in animals is still a big concern. We previously reported findings regarding a group of patients exposed to nanoparticles and presenting with an unusual disease. The reported disease was characterized by bilateral chest fluid, pulmonary fibrosis, pleural granuloma, and multiorgan damage and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
0
18
0
5
Order By: Relevance
“…This approach could have some pharmacological and toxicological applications, resulting from obtaining the distribution of nanoparticles in various tissues in small animal models and in humans. [22][23][24] …”
Section: Publish Your Work In This Journalmentioning
confidence: 99%
“…This approach could have some pharmacological and toxicological applications, resulting from obtaining the distribution of nanoparticles in various tissues in small animal models and in humans. [22][23][24] …”
Section: Publish Your Work In This Journalmentioning
confidence: 99%
“…First of all, silica and silicates have been associated with the development of lung inflammation, interstitial fibrosis, bronchitis, small airway disease, emphysema, and vascular diseases as well as immunologic reactions (Song & Tang, 2011). Recent studies showed that Th1 and Th2 cytokines may be involved in silicosis and regulatory T-cells (Treg cells) have crucial role in modulation of immune homeostasis by regulating Th1/Th2 polarization.…”
Section: Rock Wool Glass Fibers and Ceramic Fibersmentioning
confidence: 99%
“…We previously found that a group of patients exposed to PA/NPSi had pleural and pericardial effusion, pulmonary fibrosis, and granuloma, which we suspected were related to their high exposure to PA/NPSi. [9][10][11] Our present study showed that PA/NPSi caused specific toxicity presenting as pleural and pericardial effusion, fibrosis of lung and pleura, and pulmonary granuloma. These findings are almost identical to the previously reported patients.…”
mentioning
confidence: 92%
“…Furthermore, NPSi have been isolated and detected in patients' pulmonary macrophages, pleural effusions, and microvessles. 10,11 We speculate that the patients' disease could be related to their high exposure to nanomaterials in the coatings. [9][10][11] The effects of PA/NPSi on animals, as well as the acute toxicities of PA/ NPSi, are unknown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation